2001
DOI: 10.1136/ard.60.10.950
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of CD44 on monocytes and neutrophils in systemic lupus erythematosus: relations with apoptotic neutrophils and disease activity

Abstract: Background-Increased numbers of apoptotic neutrophils, and impaired monocyte/macrophage clearance of apoptotic cells, have been demonstrated in systemic lupus erythematosus (SLE). CD44 is implicated in the clearance of apoptotic neutrophils. Objective-To determine the expression of CD44 on peripheral blood monocytes and neutrophils in SLE, and examine the relations with disease activity and numbers of circulating apoptotic neutrophils. Methods-Peripheral blood was sampled from 31 patients with SLE, 19 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 44 publications
0
48
0
Order By: Relevance
“…Macrophages from SLE patients cultured in vitro are smaller, with impaired adhesion and decreased phagocytic capacity for autologous apoptotic material [28,29]. More direct evidence of the involvement of clearance deficiency in the aetiology of SLE comes from lymph node biopsy.…”
Section: Self-dsdna Released By Apoptotic Cellsmentioning
confidence: 99%
“…Macrophages from SLE patients cultured in vitro are smaller, with impaired adhesion and decreased phagocytic capacity for autologous apoptotic material [28,29]. More direct evidence of the involvement of clearance deficiency in the aetiology of SLE comes from lymph node biopsy.…”
Section: Self-dsdna Released By Apoptotic Cellsmentioning
confidence: 99%
“…Furthermore, altered monocyte phenotypes and neutropenia lead to impaired recognition and clearance of apoptotic cells, and correlate with anti-dsDNA and disease activity. 6,[9][10][11] Fas ligand (FasL), a trimeric type II membrane protein, belongs to the TNF receptor family that induces apoptosis of cells bearing Fas receptor. 12 Observations in mouse models of SLE demonstrated that mice with Fas (MRL/lpr) or FasL (gld) mutations developed lymphadenopathy with accumulation of CD4ÀCD8À double negative lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, during SLE, clearance of genetic material is delayed leading to subsequent accumulation of apoptotic cell debris, which can provoke inflammatory response and breakdown of self-tolerance [21,22]. Impaired clearance of neutrophil extracellular traps (NETs) has been described in SLE cases as well [23]. It has been suggested that reduced degradation of NETs is associated with decreased DNAse I activity which is often observed in SLE [24].…”
Section: Introductionmentioning
confidence: 99%